Immunological Dynamics Associated with Direct-Acting Antiviral Therapies in Naive and Experimented HCV Chronic-Infected Patients - Grenda Leite Pereira; Andréa Monteiro Tarragô; Walter Luiz Lima Neves; Pedro Vieira da Silva Neto; Priscila Sarmento de Souza; Juliana dos Santos Affonso; Keyla Santos de Sousa; Jéssica Albuquerque da Silva; Allyson Guimarães Costa; Flamir da Silva Victoria; Marilu Barbieri Victoria; Adriana Malheiro (Mediators of Inflammation)
The therapeutic strategies used in the treatment of hepatitis C are essentially based on the combination of direct-acting antiviral agents (DAAs). This therapy has been shown to be very effective in relation to patient adherence to treatment and has shown high rates of sustained virological response (SVR). However, the immunological dynamics of patients infected with HCV is poorly understood. This fact led us to investigate the immune system of naive and experienced patients, who we followed before the therapy and three months after the end of treatment. In this study, 35 naive and experienced Brazilian patients with chronic hepatitis C and 50 healthy donors (HD group) were studied. The analysis of the soluble immunological biomarkers was performed using the flow cytometry methodology. The SVR rate was >90% among the 35 patients. Before treatment, correlations in the naive HCV group demonstrated a mix of inflammatory response occurring with moderate correlations between chemokines, inflammatory cytokines, and Th2 profile, with a strong regulation between IL-10 and IL-17A. On the other hand, experienced patients demonstrated a poor interaction between cytokines, chemokines, and cells with a strong correlation between IL-10, IL-6, CXCL-10, and CD8+ besides the interactions between IFN-γ and IL-4. Furthermore, naive and experienced patients seem to have a distinct soluble biomarker profile; therefore, a long-term follow-up is needed to evaluate patients treated with DAAs.